2022
DOI: 10.1128/cmr.00088-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus Invasive Infections in Preterm Neonates: an Up-to-Date Review of the Literature

Abstract: Bacillus cereus group species are widespread, Gram-positive, spore-forming environmental bacteria. B. cereus sensu stricto is one of the major causes of food poisoning worldwide. In high-risk individuals, such as preterm neonates, B. cereus infections can cause fatal infections. It is important to note that the phenotypic identification methods commonly used in clinical microbiology laboratories make no distinction between B. cereus sensu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 121 publications
1
13
0
1
Order By: Relevance
“…According to previous reports [42], the fluorescence intensity of NPN could indirectly reflect the integrity of E. coli outer membrane (OM). NPN emits weak fluorescence in a hydrophilic environment, but emits sharply strong fluorescence when entering a hydrophobic environment such as the OM of E. coli.…”
Section: Antibacterial Mechanismmentioning
confidence: 83%
See 1 more Smart Citation
“…According to previous reports [42], the fluorescence intensity of NPN could indirectly reflect the integrity of E. coli outer membrane (OM). NPN emits weak fluorescence in a hydrophilic environment, but emits sharply strong fluorescence when entering a hydrophobic environment such as the OM of E. coli.…”
Section: Antibacterial Mechanismmentioning
confidence: 83%
“…Bacillus species also cause a wide variety of infections, and they are significant pathogens in humans with increasing frequency [42]. Therefore, B. subtilis was chosen as a typical Gram-positive bacterial model to explore the antibacterial ability of Ce6-TPP-PEI and TPP-PEI (4a, c).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…B. cereus is increasingly recognised as a pathogen of significance in the neonatal population. A recent review of the 145 reported cases of neonatal B. cereus cases to date describes the spectrum of disease in neonates to include bacteraemia, meningoencephalitis, pneumonia, tracheal ulceration, skin/wound infection and septic arthritis, with 80% of cases occurring in premature infants 3. Invasive respiratory infection has been described, with necrosis of the lung parenchyma and upper airway found on postmortem examinations in premature neonates 4 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus cereus consists of large, sporulating Gram-positive, rod-shaped aerobic or facultative anaerobic bacteria that are widespread in the environment (LOTTE et al, 2022). Microorganisms are ubiquitous and can contaminate various food products, leading to transient colonization of the human gut (GROSH, 1978).…”
Section: Introductionmentioning
confidence: 99%